2012
DOI: 10.22230/jripe.2012v2n2a62
|View full text |Cite
|
Sign up to set email alerts
|

South Eastern Interprofessional Collaborative Learning Environment (SEIPCLE): Nurturing Collaborative Practice

Abstract: Background: There has been tremendous pressure on Canada's healthcare system to respond to the increasingly complex health needs of the population despite worsening constraints in financial and human resources. Interprofessional collaborative practice has been seen as an enabler for improving patient care and meeting the current demands on the healthcare system. Methods:The South Eastern Interprofessional Collaborative Learning Environment (SEIPCLE) project, funded by HealthForceOntario, focused on the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In general, studies included between two to six professions. However, there were a small number of studies that included a wider professional mix: over 20 different professions groups (Curran et al 2007), 17 groups (Byrnes et al 2012) and 13 groups (Watts et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, studies included between two to six professions. However, there were a small number of studies that included a wider professional mix: over 20 different professions groups (Curran et al 2007), 17 groups (Byrnes et al 2012) and 13 groups (Watts et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of learner attitudes towards IPE was reported in a number of studies (e.g. Pollard et al 2006;Bradley et al 2009;Byrnes et al 2012). In general, it was reported that learners entered their respective IPE programmes and courses with positive attitudes, which would often diminish after participation in their respective interprofessional learning activities.…”
Section: Learner Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPC has benefits for patients, health professionals, healthcare organizations and health systems [3,4]. Studies have shown that good IPC reduces healthcare costs and expenditures, enhances quality of care and increases job satisfaction, improving staff retention and patient outcomes [5,6]. IPC responds to the shortage of financial, human, and technical resources by providing solutions that increase the effectiveness and efficiency of health services, while better responding to the complex needs of patients with chronic conditions [1,7].…”
Section: Introductionmentioning
confidence: 99%